Risk factors contributing to outer hair cell damage in children with chronic kidney disease - Hibbattino, Deon Raditya; Prasetyo, Risky Vitria; Ekorini, Haris Mayagung (Edelweiss Applied Science and Technology, 2024)
The study is aimed to assess the risk factors leading to outer hair cell damage in pediatric CKD patients. There are many similarities between the renal nephron and ear structures, making them vulnerable to same risk factors. Outer hair cell damage is frequent in pediatric patients with chronic kidney disease (CKD). A cross-sectional observational study including pediatric CKD patients. These patients underwent a hearing examination. Hearing examination using distortion product otoacoustic emissions (DPOAE) and tympanometry were performed. Other data were collected from medical records. Total of 58 children with CKD were included in this study. The incidence of hearing loss was 17,2%, with the most of hearing loss being in children underwent hemodialysis. The results showed factor associated for hearing loss in children with CKD were stage of CKD (OR: 3,178, p=0,000), the use of loop diuretic (OR:1,596, p=0,001), level of blood urea (OR:1,85, p=0,000), and duration of hemodialysis (OR 2,2, p<0,000). There is a significant increased risk to the development of outer hair cell damage in higher stage of CKD, longer use of loop diuretic, higher level of blood urea, and the longer hemodialysis duration. It is necessary to understand hearing loss is notable complication in pediatric CKD hence it is important to monitor comorbidities in pediatric patients with CKD and further research to identify risk factors for cochlear outer hair cell damage.